Study gene expression for the PelF gene responsible for the biofilm formation of Pseudomonas aeruginosa using qPCR (The Peerian Journal, 2024)
The bacterial isolates results explained that there are 66 bacterial isolates belonging to the bacterium P. aeruginosa in reality, 46 infection isolation and 20 environmental isolation. They confirmed the diagnosis using genetic diagnostics and the use of 16SrDNA and observed the appearance of one band in the drilling of the gel at the same level for all isolates. The Micro titration plates method (MTP) was used to detect isolates' ability to form the biofilm; this method gives a numerical value for the absorbency using an ELISA reader device, considered a quantitative assay, more accurate and sensitive than other methods. The isolates were diverse in forming biofilm between productive with high efficiency, medium efficiency, and low efficiency. For gene expression study for these isolates, extracted RNA was done for all isolates, then the amount of gene expression by qRT- PCR technology of PelF gene that responsible for biofilm formation for studied samples that represented by 56 isolates as treatment isolates and ten isolates as control isolates of each gene using the One Step Real-time–PCR and all samples were genetically expressive, with varied results of gene expression between high samples of expression and medium of expression and a weak expression, with highly significant differences and probability (P